-2 and 1.
Hope this helps!
Answer:
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Step-by-step explanation:
Given equation is ![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
Factor denominators then solve by making denominators equal
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![\frac{y\left(y+4\right)-4\left(y-4\right)}{\left(y-4\right)\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%7D%7B%5Cleft%28y-4%5Cright%29%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![y\left(y+4\right)-4\left(y-4\right)=9](https://tex.z-dn.net/?f=y%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%3D9)
![y^2+4y-4y+16=9](https://tex.z-dn.net/?f=y%5E2%2B4y-4y%2B16%3D9)
![y^2=9-16](https://tex.z-dn.net/?f=y%5E2%3D9-16)
![y^2=-7](https://tex.z-dn.net/?f=y%5E2%3D-7)
take squar root of both sides
![y=\pm \sqrt{-7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20%5Csqrt%7B-7%7D)
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Hence final answer is
.
Answer:
Equation: y=2/3x-4
y intercept is (0,-4)
x intercept is (6, 0)
Step-by-step explanation:
Answer:
2268 grams or 2 kg 268 g
Step-by-step explanation:
<u>How to convert Pounds to Grams</u>
1 pound (lb) is equal to 453.59237 grams (g).
1 lb = 453.59237 g
The mass m in grams (g) is equal to the mass m in pounds (lb) times 453.59237:
m(g) = m(lb) × 453.59237
In this case,
Convert 5 lb to grams:
2267.96 approximately convert to nearest thousands.
m(g) = 5 lb × 453.59237 = 2268 g or 2 kg 268 g
Answer:
no
Step-by-step explanation:
541982/3 = 180,660.667